2012
DOI: 10.1128/aac.01606-12
|View full text |Cite
|
Sign up to set email alerts
|

Full and Broad-Spectrum In Vivo Eradication of Catheter-Associated Biofilms Using Gentamicin-EDTA Antibiotic Lock Therapy

Abstract: Biofilms that develop on indwelling devices are a major concern in clinical settings. While removal of colonized devices remains the most frequent strategy for avoiding device-related complications, antibiotic lock therapy constitutes an adjunct therapy for catheter-related infection. However, currently used antibiotic lock solutions are not fully effective against biofilms, thus warranting a search for new antibiotic locks. Metal-binding chelators have emerged as potential adjuvants due to their dual anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 51 publications
4
49
0
Order By: Relevance
“…In an animal study, Chauan et al [22] showed that gentamicin-EDTA lock therapy is active against S. aureus and CoNS biofilms. Fortun et al used this compound as ALT for 14 days, in association with systemic treatment, for gram-negative rod CLABSI.…”
Section: Aminoglycosidesmentioning
confidence: 98%
“…In an animal study, Chauan et al [22] showed that gentamicin-EDTA lock therapy is active against S. aureus and CoNS biofilms. Fortun et al used this compound as ALT for 14 days, in association with systemic treatment, for gram-negative rod CLABSI.…”
Section: Aminoglycosidesmentioning
confidence: 98%
“…Several in vitro and in vivo studies demonstrated the presence of highly tolerant bacterial persisters in biofilms formed by Gram-positive and Gram-negative pathogens (86)(87)(88)(89). Clinical demonstration of the presence of persisters can be inferred from the risk of infection recurrence during biofilm-related infections.…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%
“…Using a rat model of biofilm-related infection with a totally implantable venous access port (TIVAP), it was recently shown that the gentamicin-EDTA combination was the most effective lock solution compared to gentamicin alone, EDTA alone, or ethanol (70%) (87,344). Gentamicin-EDTA is therefore a potential lock solution able to cure highly tolerant biofilms and eradicate persistent bacteria, thereby preventing recurrence of Gram-positive as well as Gram-negative bacterial biofilms on TIVAP (344).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…In previous studies, the most common infectious agent is reported as S. epidermidis in port catheter related infections 15,25 . Also, coagulase negative staphlococci (S. epidermidis, S. hominis, S. saprophyticus) were reported as the most common microbial organisms 22 .…”
Section: Discussionmentioning
confidence: 99%